AGES CHALLENGES OF THE AGING CULTURE FROM A GENDER-GENERATION PERSPECTIVE: ATTITUDES OF YOUNG PEOPLE TOWARDS AND THE ELDERLY (Heritage, 2021)
The culture of aging is considered being an inseparable domain and aspect of modern concept of living. It has become foundation of sustainable development policy and a measure for evaluating the quality of social relations and human potential of an inclusive society. As an international perspective for alleviating age inequality, there is a need to redefine the social and political economy of aging in a global context.Analysing youth (secondary school and faculty students) impressions of gender and intergenerational similarities as well as their differences in concept of aging was the main problem of our research. We investigated youth’s general attitudes towards old people in order to discover if there are age and gender presumptions in youngsters that influence evaluating elders’ characters in contrast with their peers as well as personal qualities between old men and women.
Keywords: ageism, aging and gender stereotypes, intergenerational gap.